Introduction: New Directions in ADR and Clinical Legal Education - Karen Tokarz; Annette Ruth Appell (Washington University Journal of Law & Policy, 2010)
The authors in this volume are in the forefront of innovative teaching, practice, and scholarship in dispute resolution and clinical education. In their articles, they eloquently highlight the important goals shared by dispute resolution and clinical legal education—to foster creative problem solving, to empower clients and advance the interests of parties, to promote social justice, and to enhance ethical practice and professionalism. The authors illuminate new and exciting ways in which dispute resolution and clinical education, jointly and severally, can inform, improve, and reform not only legal education, but also the practice of law, the legal profession, and systems of justice.
Keywords: Legal clinics; Alternative dispute resolution; ADR; Legal education